2017
DOI: 10.1111/nmo.13132
|View full text |Cite
|
Sign up to set email alerts
|

A randomized placebo‐controlled trial on the effects of Menthacarin, a proprietary peppermint‐ and caraway‐oil‐preparation, on symptoms and quality of life in patients with functional dyspepsia

Abstract: Menthacarin is an effective therapy for the relief of pain and discomfort and improvement of disease-specific QoL in patients with FD and significantly improves symptoms consistent with EPS and PDS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
54
1
11

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 115 publications
(70 citation statements)
references
References 45 publications
(57 reference statements)
4
54
1
11
Order By: Relevance
“…The studies published between 1991 and 2019 were included. Patients had FD, [15][16][17][18][19][20][21][22]13,14,[23][24][25][26][27][28][29][30][31][32] and constipation [56][57][58][59][60][61][62] in 19, 23 and 7 trials respectively. More than 33 different kinds of herbal formulae were tested in the included trials.…”
Section: Resultsmentioning
confidence: 99%
“…The studies published between 1991 and 2019 were included. Patients had FD, [15][16][17][18][19][20][21][22]13,14,[23][24][25][26][27][28][29][30][31][32] and constipation [56][57][58][59][60][61][62] in 19, 23 and 7 trials respectively. More than 33 different kinds of herbal formulae were tested in the included trials.…”
Section: Resultsmentioning
confidence: 99%
“…May et al reported a strong improvement in 66% of the patients after peppermint/caraway oil treatment compared to 20.9% after placebo . Furthermore, Rich et al reported an improvement in FD symptoms of more than 10% in 88% of the patients after peppermint/caraway oil treatment compared to 55.4% after placebo . Lastly, Chey et al confirmed the superiority of peppermint/caraway oil treatment over placebo, showing symptom improvement in 78% of PDS patients and 72% of EPS patients compared to 50% and 40% in the control groups, respectively .…”
Section: Current Treatment Options For Functional Dyspepsiamentioning
confidence: 97%
“…Für dieses Produkt liegt eine Reihe von Studien vor, in denen sich u. a. im Vergleich zu dem früher üblichen Cisaprid eine vergleichbare [27] und vs. Placebo eine sehr gute [29], [30], [34] Wirksamkeit zeigte, sogar auch bei der Langzeitanwendung von bis zu 12 Monaten [17], [43] bei nicht säurebedingter funktioneller Dyspepsie, in einer Studie auch bei chronisch-entzündlichen Darmerkrankungen [4]. Eine jüngere Analyse der Daten aus 3 Studien (Metaanalyse von Subgruppen) ergab zudem eine Wirkung (Zielgröße: Schmerzempfinden) bei Dyspepsie-Patienten mit typischen Symptomen eines Reizdarms [28].…”
Section: Wirkungenunclassified